Plagiarism and predatory journals: A threat to scientific integrity - María Francisca Abad-García (Elsevier, 2019)
This article presents an analysis of the concept of plagiarism in order to show the wide spectrum of manifestations that can be considered as such when committing a transgression of intellectual property, carried out with the intention of deceiving the authors' true contribution and the originality and novelty of the information. It describes the different circumstances in which intentional plagiarism has occurred, and the damage that this misconduct causes in the credibility of the scientific system, in which authorship credit is the foundation of the academic career, of the prestige of the author in the scientific community, and the basis for financing research. Some circumstances are favouring this fraud: the pressure exerted on researchers by the criteria used for promotion and reward that prioritise the quantity of works on their quality, the existence of a market for the purchase and sale of scientific articles, and the proliferation of predatory journals that operate with no or minimal ethical standards. Finally, the paper highlights the convenience of the adoption of criteria that prioritise the intrinsic quality of the work versus its quantity, including the active involvement of the institutions in the development of active policies for the prevention, detection, and punishment of the cases of potential fraud, and to emphasise that, in the end, the prevention of fraud relies on the individual adoption of ethical and responsible behaviour. Resumen: Este artículo propone un análisis del concepto del plagio con la finalidad de mostrar el amplio espectro de manifestaciones que pueden ser consideradas como tal al incurrir en una transgresión de la propiedad intelectual, realizada con el ánimo de engañar sobre la verdadera contribución de los autores y sobre la originalidad y novedad de la información.Describe las distintas circunstancias en las que se incurre en un plagio intencional y el daño que esta mala conducta ocasiona en la credibilidad de un sistema científico, en el que el crédito de autoría es el fundamento de la carrera académica, del prestigio del autor en la comunidad científica y la base para la financiación de la investigación.Se consideran como factores favorecedores de este fraude la presión que ejercen sobre los investigadores los criterios utilizados para la promoción y recompensa que priorizan la cantidad de trabajos sobre su calidad, la existencia de un mercado de compra-venta de artículos científicos y la proliferación de las revistas depredadoras que funcionan con nulos o mínimos estándares éticos.Finalmente se incide en la necesidad de adoptar medidas que contribuyan a la prevención y detección temprana del fraude, resaltando la necesidad de la adopción de criterios que prioricen la calidad intrínseca de los trabajos frente a su cantidad, de una implicación activa de las instituciones en el desarrollo de políticas activas para su prevención, detección y castigo y en la toma de conciencia de que la prevención del fraude reside en la adopción individual de un comportamiento ético y responsable.